Inner and outer segment junction (IS/OS line) integrity in ocular Behçet's disease - Yüksel,Harun (2014)
Purpose: In this study, we examined the spectral domain optical coherence tomography (OCT) findings of ocular Behçet's disease (OB) in patients with inactive uveitis. Specifically, we analyzed the inner and outer segment junction (IS/OS line) integrity and the effect of disturbed IS/OS line integrity on visual acuity. Methods: Patient files and OCT images of OB patients who had been followed-up between January and June of the year 2013 at the Dicle University Eye Clinic were evaluated retrospectively. Sixty-six eyes of 39 patients were included the study. Results: OCT examination of the patients with inactive OB revealed that approximately 25% of the patients had disturbed IS/OS and external limiting membrane (EML) line integrity, lower visual acuity (VA), and lower macular thickness than others. Linear regression analysis revealed that macular thickness was not an independent variable for VA. In contrast, the IS/OS line integrity was an independent variable for VA in inactive OB patients. Conclusion: In this study, we showed that the IS/OS line integrity was an independent variable for VA in inactive OB patients. Further prospective studies are needed to evaluate the integrity of the IS/OS line in OB patients.